2012
DOI: 10.1021/ja208694g
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of Substrate Inhibition in Human Indoleamine 2,3-Dioxygenase

Abstract: Indoleamine 2,3-dioxygenase catalyzes the O2-dependent oxidation of l-tryptophan (l-Trp) to N-formylkynurenine (NFK) as part of the kynurenine pathway. Inhibition of enzyme activity at high l-Trp concentrations was first noted more than 30 years ago, but the mechanism of inhibition has not been established. Using a combination of kinetic and reduction potential measurements, we present evidence showing that inhibition of enzyme activity in human indoleamine 2,3-dioxygenase (hIDO) and a number of site-directed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
94
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(105 citation statements)
references
References 26 publications
10
94
1
Order By: Relevance
“…63 Moreover, substrate inhibition is a recurrent theme in these studies of dioxygenases, as is observed in DHP as well. 13,64 ■ CONCLUSION The present study permits a comparison of substrates and inhibitors that have different modes of binding. Both substrates and inhibitors bind in the distal pocket of the DHP protein in sites we call the α-and β-sites in Figure 1.…”
Section: ■ Discussionmentioning
confidence: 98%
“…63 Moreover, substrate inhibition is a recurrent theme in these studies of dioxygenases, as is observed in DHP as well. 13,64 ■ CONCLUSION The present study permits a comparison of substrates and inhibitors that have different modes of binding. Both substrates and inhibitors bind in the distal pocket of the DHP protein in sites we call the α-and β-sites in Figure 1.…”
Section: ■ Discussionmentioning
confidence: 98%
“…On the basis of equilibrium binding studies, Sono et al [136] proposed that the ferrous enzyme binds first with L-Trp and then with O 2 [136]. However, a more recent study that combined kinetic and electrochemical measurements showed that, at low concentrations of L-Trp, O 2 binds first followed by L-Trp binding, but, at higher L-Trp concentrations, the binding order is reversed [137]. Resonance Raman spectroscopic data for the Fe II -O 2 complex of human recombinant IDO1 indicated that it is best described as an Fe III -O 2…”
Section: Control Of Ido1 Gene Expressionmentioning
confidence: 99%
“…Notably the ternary complex resulted in ordering a loop adjacent to the active site [15]. Measurement of binding affinity suggested an obligate order of substrate binding, with CN binding first [15], which was also recently shown to be the case for TDO [16]. Unusually, when bound to PrnB, CN adopted a bent conformation (like that expected for oxygen), with the nitrogen pointing towards an oxyanion hole.…”
Section: Prnb An Unexpected Addition To the Familymentioning
confidence: 81%